Imagination wide open: accessibility project in Bragança's Contemporary Art Museum - Martins, Cláudia (2019)
Museums are intensely visual places and traditionally not accessible to people with impairments, although many cultural institutions have made it their job to go the extra mile so as to include ALL people. These have been a source of inspiration for a myriad of professionals, trainers and visitors. The new millennium stands for the mushrooming of multisensory experiments, participatory exhibitions, all of which attempt to heed people’s concerns, needs and views. It is in the light of these principles that we aim to report on an ongoing accessibility project, within the master’s degree in Translation, at a local museum of contemporary art in Bragança – the Museum of Contemporary Art Graça Morais. The first stage intended to ascertain the willingness of the museum to develop a project for the blind and visually-impaired and then the museum’s accessibility conditions, by means of a diagnosis form. This was followed by the pilot test for an exhibition, named “Humanity” (painter Graça Morais, 2018; curatorship by Jorge Costa, 2018; production by the City Council of Bragança, 2018), which consisted of an audio visit for a group of three blind people, including orientation audiodescription through the 7 rooms of the exhibition and replacement audiodescription for the selected pieces. The second stage of this project will be directed to a new exhibition – “Blue Eyes of the Sea” (painter Graça Morais, 2005; curatorship by Jorge Costa, 2019; production by the City Council of Bragança, 2019) – which shall offer an audiodescribed visit by means of a QR code, in Portuguese, English and Spanish.